Strategies to Develop Technopreneurship in College (Best Practices in the Implementation of Community Service Through the Entrepreneurship Development Program Scheme) - Dewanto; Nanik Indahwati; Sri Handajani (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
The number of Indonesian entrepreneurs is still 3.1% of the total population. Whereas in developed countries, at least 14% of the population are entrepreneurs. For this reason, the government through various programs is trying hard to accelerate its development. One of them is through the Entrepreneurship Development Program (EDP) which is implemented in several universities, including the Surabaya State University (Unesa). The purpose of writing this article is to describe Unesa's practical experience in implementing EDP which includes: 1) the right strategy in developing technopreneurs; 2) Newly developed Technopreneursh, and 3) Establishment of a new entrepreneurial incubator. The method used in implementing this EDP is the PALS (Participatory Action Learning System) method which includes three phases, namely: 1) awareness); 2) capacity, and scaffolding entrepreneurship capacity building, and (3) institutionalization. The results of the EDP implementation show; 1) found new strategies in developing technopreneurs; 2) Ten (10) tenants become new technopreneurs, and 3) The establishment of a new entrepreneurial incubator center on the Ketintang campus. The EDP program was implemented 100% according to the target. Many thanks go to the Directorate of Research and Community Service(DRCS) for funding the implementation of this program.